2011
DOI: 10.1371/journal.pone.0019985
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting-State Perfusion after Repeated Encoding Is Related to Later Retrieval of Declarative Associative Memories

Abstract: Electrophysiological studies in animals have shown coordinated reactivation of neuronal ensembles during a restricted time period of behavioral inactivity that immediately followed active encoding. In the present study we directly investigated off-line processing of associative memory formation in the human brain. Subjects' regional cerebral blood flow (rCBF) as a surrogate marker of neural activity during rest was measured by MR-based perfusion imaging in a sample of 14 healthy male subjects prior to (Pre2) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
1
13
1
Order By: Relevance
“…Specifically, it has been hypothesized that time periods that engender a reduction in environmental stimulation may allow for the expression of physiological mechanisms underlying memory consolidation (3,40). Additionally, robust and reliable patterns of connectivity are known to occur during awake rest (41,42), and several recent studies have shown that overall univariate measures of blood flow, BOLD responses, and BOLD connectivity during awake rest may be modulated in a manner consistent with memory consolidation (21)(22)(23)(24)(25). Here, we extend these results by showing that multivariate encoding-related hippocampal BOLD patterns persist into awake rest periods and that this persistence is related to future overall memory for prerest experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, it has been hypothesized that time periods that engender a reduction in environmental stimulation may allow for the expression of physiological mechanisms underlying memory consolidation (3,40). Additionally, robust and reliable patterns of connectivity are known to occur during awake rest (41,42), and several recent studies have shown that overall univariate measures of blood flow, BOLD responses, and BOLD connectivity during awake rest may be modulated in a manner consistent with memory consolidation (21)(22)(23)(24)(25). Here, we extend these results by showing that multivariate encoding-related hippocampal BOLD patterns persist into awake rest periods and that this persistence is related to future overall memory for prerest experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Critical for theories of consolidation, the extent of hippocampal reactivation in rodents has recently been related to spatial memory improvements (17), whereas interference with putative reactivation events leads to impairments in learning (18)(19)(20). Prior work in humans using functional MRI (fMRI) has shown that resting connectivity between the hippocampus and encoding-related cortical areas can be modulated by an associative encoding experience (21,22) and that these experience-related changes are correlated with later memory (21,23). Additionally, overall changes in activity and connectivity in the hippocampus and cortical regions have been shown to occur during slowwave sleep and subsequent task performance (24,25).…”
mentioning
confidence: 99%
“…Third, resting state data was acquired after the memory task. The ordering of these tasks has been shown to have an impact on connectivity of the DMN (Groen et al, 2011). We adopted this methodology as a strategy to reduce the time between training and performance on the task.…”
Section: Discussionmentioning
confidence: 99%
“…The goal of this design was to reduce the delay between instruction and practice for the task and engagement in the in-scanner task. Although Groen, Sokolov, Jonas, Roebling, & Spitzer (2011) showed evidence that post-learning resting state data can be influenced by the preceding cognitive task, Grady et al (2010) were able to extract the core components of the DMN even during fixations that were interspersed between tasks. This suggests that the key components of the DMN are robust even when collected after a task has been administered.…”
Section: Methodsmentioning
confidence: 98%
“…In conclusion, transport information like warnings and how to behave in disasters (evacuation, sheltering, iodine blockade and food ban) to the public in a way that it will be perceived, keep it simple, straight forward and repeat it to gain statistical significant levels for brain memory cells in the hippocampus [36].…”
Section: Resultsmentioning
confidence: 99%